Smokeless tobacco use among United States Air Force trainees. Issue 3 (July 2017) - Linde, Brittany D.; Ebbert, Jon O.; Schroeder, Darrell R.; Hanson, Andrew C.; Talcott, G. Wayne; Klesges, Robert C.
Background: The prevalence of smokeless tobacco use in the United States Air Force (USAF) exceeds civilian use rates. The prevalence and correlates of smokeless tobacco use were assessed and evaluated in a sample of USAF trainees. Methods: We conducted a cross-sectional survey of USAF technical training school personnel at Joint Base San Antonio-Lackland and Fort Sam Houston ( N = 14, 810). Survey completion rate was 78%. Logistic regression was used to analyze the associations between demographic variables, tobacco use, and social factors for both regular and infrequent smokeless tobacco (e.g., chewing tobacco, snuff) users. Results: Overall, 16% of Airmen had ever used smokeless tobacco and 10% regularly used smokeless tobacco. In multivariate analyses, men had greater odds than women of regular smokeless tobacco use (adjusted odds ratio [OR] = 15.2; 95% confidence interval [CI]: 10.8–21.5) and infrequent smokeless tobacco use (adjusted OR = 4.2; 95% CI: 3.1–5.7). Smokeless tobacco use was associated with participation in high school sports (adjusted OR = 1.9; 95% CI: 1.6–2.3 for regular users; adjusted OR = 1.4; 95% CI: 1.1–1.7 for infrequent users), smoking cigarettes (adjusted OR = 4.3; 95% CI: 3.6–5.1 for regular users; adjusted OR = 4.0; 95% CI: 3.2–5.0 for infrequent users), or living with someone who used smokeless tobacco (adjusted OR = 2.2; 95% CI: 1.9–2.6 for regular users; adjusted OR = 1.4; 95% CI: 1.1–1.7 for infrequent users). Black or African Americans were less likely than whites to be regular (adjusted OR = 0.3; 95% CI: 0.1–0.4) or infrequent (adjusted OR = 0.3; 95% CI: 0.2–0.4) users of smokeless tobacco. Conclusions: Smokeless tobacco use among incoming Air Force recruits is common and negatively impacts the Air Force's goal to be tobacco-free. Understanding sociodemographic characteristics perpetuating smokeless tobacco use in the Air Force population can inform the development of health promotion interventions.